MODEL PARTICIPATION ACTION RESEARCH (PAR) AS A METHOD FOR DEVELOPING ENVIRONMENTAL ARTS IN NANGGALAMEKAR VILLAGE, CIANJUR - Cahyana, Agus; Sriwardani, Nani (CAIJ: Creative Arts Interdisciplinary Journal, 2022)
This study aims to determine the implementation of the Participation Action Research (PAR) approach as a method of developing environmental artworks in the village of Nanggalamekar. This study uses a qualitative approach with a PAR research model design, the research location is in Nanggalamekar Village, Ciranjang District, Cianjur Regency. Data collection techniques using observation, interviews, and documentation. The research subjects were Village Management, PKK, Youth Organizations, community leaders, partners, and training participants. The technique used is purposive sampling, and data analysis used descriptive qualitative analysis. Through the Environmental Arts program, the community is invited to revisit their environment and how the environment in which they live becomes an interesting thing to display in the form of art so that it can become a means of learning about the environment, culture, as well as empowering the community to care for the environment and explore the economic potential in the environment. they stay. Environmental art is done by utilizing all objects that exist around our environment, can be in the form of plant objects, wood, stone, soil, or other natural objects. Other objects that can also be used are unused objects, such as used cans and others. Through this environmental arts program, it is hoped that the community will be more familiar with the potential of their natural environment that can be used more productively, both as a means of conveying artistic and cultural values and as a creative means that has an economic impact. The results showed that action research is an alternative research method in the study and action of community empowerment. Action research is based on the assumption that research should be linked to a change agenda in society. Action research is carried out not only to obtain the truth but also to create the expected conditions. Action research can be used effectively in studies and community empowerment actions given its characteristics that emphasize active community participation. Through action research, it will be possible to produce a formula that is by the conditions of the community in carrying out community empowerment efforts. The PAR model formulated with the development of environmental works of art in Nanggalamekar found that at the reflection stage it was necessary to monitor and evaluate the planning and action stages to know the outputs and outcomes of research and training activities that have been carried out. Keywords: Art, Environment, Community Empowerment, Community Participation